The atlas of the world's worst natural disasters - Newson, Lesley (A Dorling Kindersley Book, 1998)
Riveting accounts of what happened during the world's most significant natural disasters, covering everything from volcanic eruptions to meteorite strikes this illustrated book pinpoints the locations of over 500 upheavals to afflict the Earth since prehistoric times